Family physicians' views on their role in the management of childhood obesity: a mixed methods study from Turkey - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2018)
Background: Childhood obesity (CO) is a high priority issue due to its serious health consequences and its rapid increase. Objectives: To examine the views of primary care physicians (family physicians, FPs) in Turkey regarding their role in the management of CO and the barriers they perceive. Methods: Mixed methods approach. Data was collected in two major counties of Istanbul between February and May 2014. All Family Health Centres (FHCs) in the region were visited, and 180/284 FPs (63.4%) agreed to complete a structured questionnaire (22 questions). Of those, 48 FPs agreed to participate in in-depth interviews that were taken until saturation was 25. Quantitative data were analysed using descriptive statistics. For qualitative data, content analysis was applied to identify the themes. Results: Most of the FPs (93.3%) agreed that they have a role in managing CO. Almost all FPs (98.3%) agreed that for the 0-4-year-olds height and weight measures should be taken. However, only 67.6% recommended this for children aged 5-15 years. The most common barriers in the management of CO were reported as lack of time (68.9%) and FHCs not being utilized for the care of children aged 5-15 years old (53.3%) in Turkey. In-depth interviews showed that FPs tend to limit their role to identifying the problem and making the family aware of it. Conclusion: Although FPs recognize primary healthcare as an appropriate setting for managing CO, they have concerns about being involved in the treatment.
Keywords: Child obesity; mixed methods; parents; primary care physicians; Turkey; PRIMARY-CARE; GENERAL-PRACTITIONERS; ADOLESCENT OVERWEIGHT; DIAGNOSIS; ATTITUDES; CHILDREN